Báo cáo đánh giá tác động chính sách của dự án Luật Đất đai (sửa đổi) (Số: 116/BC- BTNMT) - Bộ Tài nguyên và Môi trường (2022)
Toàn văn Báo cáo đánh giá tác động chính sách của dự án Luật Đất đai (sửa đổi) (Số: 116/BC- BTNMT)